2021
DOI: 10.3390/ijms222312989
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and DNA Methylation in Humans

Abstract: Physical activity is a strong stimulus influencing the overall physiology of the human body. Exercises lead to biochemical changes in various tissues and exert an impact on gene expression. Exercise-induced changes in gene expression may be mediated by epigenetic modifications, which rearrange the chromatin structure and therefore modulate its accessibility for transcription factors. One of such epigenetic mark is DNA methylation that involves an attachment of a methyl group to the fifth carbon of cytosine res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Research interest into how exercise affects genome-wide skeletal muscle DNA methylation has increased in recent years, and multiple associated reviews have been published [25,[44][45][46]. Barres et al [19] were the first to report that the hypomethylation of various metabolic genes occurs in skeletal muscle following a single high-intensity aerobic exercise session in humans, and that these events corresponded with an alteration in the mRNA expression levels of these genes.…”
Section: Insert Table 2 Here Discussionmentioning
confidence: 99%
“…Research interest into how exercise affects genome-wide skeletal muscle DNA methylation has increased in recent years, and multiple associated reviews have been published [25,[44][45][46]. Barres et al [19] were the first to report that the hypomethylation of various metabolic genes occurs in skeletal muscle following a single high-intensity aerobic exercise session in humans, and that these events corresponded with an alteration in the mRNA expression levels of these genes.…”
Section: Insert Table 2 Here Discussionmentioning
confidence: 99%
“…It seems that the sedentary lifestyle is correlated with an unfavorable epigenome. Exercise has been shown to increase DNA methylation in peripheral blood cells and alter histone acetylation (lysine 36-H3 acetylation) [ 17 , 118 , 119 ]. Other studies suggest that exercise induces both dynamic changes in H4 deacetylation/loss of promoter methylation and transient changes in miRNA expression profiles [ 17 , 118 ].…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Exercise has been shown to increase DNA methylation in peripheral blood cells and alter histone acetylation (lysine 36-H3 acetylation) [ 17 , 118 , 119 ]. Other studies suggest that exercise induces both dynamic changes in H4 deacetylation/loss of promoter methylation and transient changes in miRNA expression profiles [ 17 , 118 ]. Identifying the dynamics of epigenetic regulation could allow for effective therapeutic interventions involving the direct modulation of gene expression by modifying environmental factors [ 17 , 119 , 120 ].…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Additionally, in the present study, both HbSS and HbSC groups showed statistically significant DMPs distribution in the regions related to CpG Island with hypermethylation at CpG Island and S_Shore regions, and hypomethylation at Open Sea region. Approximately 60–70% of the genes in the human genome present CpGs Island, especially in promoter regions, and its methylation is closely associated to gene silencing [ 51 ].…”
Section: Discussionmentioning
confidence: 99%